ASSORTMENT POLICY OF TEXTILE ENTERPRISES AND SCIENTIFIC APPROACHES TO ITS MANAGEMENT (Marketing Journal, 2025)
This article examines the theoretical and practical aspects of forming and managing the assortment policy of textile enterprises. The assortment policy is considered as a key factor in ensuring the competitiveness of enterprises in the market. Indicators s uch as stability, completeness, renewability, and consistency are scientifically analyzed. The study applies a systematic approach, economic analysis, and marketing modeling methods to evaluate assortment management efficiency. By determining the stability, completeness, and renewal coefficients, the conformity of the product portfolio to market demand and the effectiveness of enterprise operations were assessed. The research also provides practical recommendations for assortment renewal and diversification, taking into account innovative approaches, product design, and consumer preferences. The results contribute to the scientific justification of planning and optimizing assortment policy in textile enterprises.
Keywords: textile industry; assortment policy; stability coefficient; completeness indicator; renewal index; assortment management; market demand; innovative approach; marketing strategy